Discordance between histopathology and immunohistochemistry and pattern of lymphoma in northern part of Bangladesh - Sarkar, Surozit Kumar; Shafiul Azam, M.; Islam, Khaza Amirul; Reza, Samim; Biswas, Showrab; Al Shafi, Imtiaz (International Journal of Research in Medical Sciences, 2025)
Background: Even in this modern era, many lymphoma patients are getting treatment based on histopathology diagnosis. The treatment plan and overall survival (OS) of lymphoma patients are adversely affected by either misdiagnosis or overdiagnosis. This study is intended to evaluate the degree of discordance between IHC and histopathological investigations, the pattern of lymphoma and various factors related to it. Methods: This cross-sectional study was conducted in the Department of Hematology, Shaheed Ziaur Rahman Medical College Hospital, Bogura and private practice from 2019 to 2024 until 100 cases were available. Variation in diagnosis was assessed and factors such as cellular origin of lymphoma, status of CD20 positivity, any role of expert variation and justification of histopathology as a tool of treatment were assessed. Data were collected by reviewing investigation reports and documented in a checklist. Results: Diagnostic discordance, regarding confirmed diagnosis, between histopathology and IHC was identified in 78% of patients. In 58% of cases, morphological diagnosis even failed to clarify broadly if it is malignant or not, if it is lymphoma whether it is HL or NHL. In 75% of lymphoma cases, peripheral lymph node involvement was found, about 10% of cases NHL involved bone marrow rather than peripheral LNs. CD20 was positive in 62% of lymphomas, 10% of HD and 72% of NHL. Conclusions: Lymphoma is a potentially curable malignancy having a wide variety of treatment options depending on the type of disease. This typing is not possible without IHC. No lymphoma patient should be treated without IHC diagnosis.